Considerations for Improved Mobile Health Evaluation: Retrospective Qualitative Investigation - Dick, Samantha; O'Connor, Yvonne; Thompson, Matthew J; O'Donoghue, John; Hardy, Victoria; Wu, Tsung-Shu Joseph; O'Sullivan, Timothy; Chirambo, Griphin Baxter; Heavin, Ciara (JMIR Publications, 2020)
BackgroundMobile phone use and, consequently, mobile health (mHealth) interventions have seen an exponential increase in the last decade. There is an excess of 318,000 health-related apps available free of cost for consumers to download. However, many of these interventions are not evaluated and are lacking appropriate regulations. Randomized controlled trials are often considered the gold standard study design in determining the effectiveness of interventions, but recent literature has identified limitations in the methodology when used to evaluate mHealth. ObjectiveThe objective of this study was to investigate the system developers' experiences of evaluating mHealth interventions in the context of a developing country. MethodsWe employed a qualitative exploratory approach, conducting semistructured interviews with multidisciplinary members of an mHealth project consortium. A conventional content analysis approach was used to allow codes and themes to be identified directly from the data. ResultsThe findings from this study identified the system developers' perceptions of mHealth evaluation, providing an insight into the requirements of an effective mHealth evaluation. This study identified social and technical factors which should be taken into account when evaluating an mHealth intervention. ConclusionsContextual issues represented one of the most recurrent challenges of mHealth evaluation in the context of a developing country, highlighting the importance of a mixed method evaluation. There is a myriad of social, technical, and regulatory variables, which may impact the effectiveness of an mHealth intervention. Failure to account for these variables in an evaluation may limit the ability of the intervention to achieve long-term implementation and scale.